Forms Of Legal Protection Of The Identity Of The Child Who Is Dealing With The Law - Supriyadi, Supriyadi (Universitas Dharmawangsa, 2022)
The identity of the child who is facing the law for the crime of molestation really needs to be protected and kept secret because for the future. Avoid the negative stigma that children face. The problem raised in this thesis is how the form of ethical violations against the publication of the identity of children who are faced with the law?. What is the form of legal protection for the identity of a child who is dealing with the law? How is the application of sanctions against the media that disseminate the identity of children who face the law?.The research method used in this study is normative juridical research. Normative legal research is secondary data. The nature of this study is descriptive analysis. Data collection techniques this study was conducted by the method of library research (library research). The form of ethical violations against the publication of the identity of children who are faced with the law are:the identity of the child, namely the name of the victim/perpetrator, the name of the perpetrator's parents, the name of the victim's parents, the face of the victim's child, the face of the perpetrator's child, the address of the perpetrator's child and the victim's child. Must be kept secret is that the identity of the child who is dealing with the law that must be kept secret was disclosed in the print media and electronic media.The form of legal protection for the identity of children who are faced with the law is to be treated humanely by paying attention to their age-appropriate needs, separated from adults, obtaining legal assistance and other assistance effectively, conducting recreational activities, free from torture, punishment or other inhumane cruel treatment and degrading their degree and dignity, not sentenced to death or life imprisonment, not arrested, detained, or imprisoned, except as a last resort in the shortest possible time, obtain justice in the face of an objective impartial children's court and in a hearing that is closed to the public, not published identity, obtain the assistance of parents / guardians and people trusted by the child, obtain social advocacy, obtain private life , obtain accessibility, especially for children with disabilities, obtain education, obtain health services, obtain other rights in accordance with the provisions of legislation.